2011
DOI: 10.1007/s12079-011-0130-6
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-translational regulation of osteopontin in cancer

Abstract: Osteopontin (OPN) is a matricellular protein that binds to a number of cell surface receptors including integrins and CD44. It is expressed in many tissues and secreted into body fluids including blood, milk and urine. OPN plays important physiological roles in bone remodeling, immune response and inflammation. It is also a tumour-associated protein, and elevated OPN levels are associated with tumour formation, progression and metastasis. Research has revealed a promising role for OPN as a cancer biomarker. OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 115 publications
(238 reference statements)
3
88
0
1
Order By: Relevance
“…In addition, a number of studies have demonstrated that OPN promoted tumor invasion and metastasis and regulated MMP-9 secretion (27)(28)(29)(30)(31). OPN was shown to combine with integrin αvβ3 and activate NF-κB (nuclear factor-κB) through the PI3K/Akt/IKK (κB kinase inhibitor) signaling pathway, increasing the secretion of urokinase-type plasmi nogen activator A (uPA) and promoting tumor invasion (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of studies have demonstrated that OPN promoted tumor invasion and metastasis and regulated MMP-9 secretion (27)(28)(29)(30)(31). OPN was shown to combine with integrin αvβ3 and activate NF-κB (nuclear factor-κB) through the PI3K/Akt/IKK (κB kinase inhibitor) signaling pathway, increasing the secretion of urokinase-type plasmi nogen activator A (uPA) and promoting tumor invasion (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, the N-terminal region adjacent to the signal peptide that is affected by splicing lacks any known ligand binding domains (64), although this region does include O-linked glycosylation and phosphorylation sites, and may also contain sites of interaction with the ECM (26). According to Anborgh et al, the exon labelled 'exon 5' in Figure 1 contains glutamine residues that undergo crosslinking by transglutaminase (31). This exon is absent in both OPN-c and OPN-4 variants, suggesting that these variants may be unable to form polymeric structures (Table 2 and Figure 1).…”
Section: Osteopontin Splice Variantsevidence For Association With Spementioning
confidence: 99%
“…While the predicted molecular weight of the proteins encoded by the five identified OPN splice variants ranges from 30.8 kDa (OPN-4) to 37.2 kDa (OPN-5; predicted molecular weights calculated using Expasy), the primary observed band in western blotting is typically around 70 kDa, and multiple bands ranging from 41 to 75 kDa are frequently observed (31). However, OPN undergoes extensive post-translational modification, with serine/threonine phosphorylation, glycosylation, tyrosine sulfation and cross-linking, and OPN is also a substrate for thrombin and matrix metalloproteinases (MMPs).…”
Section: Osteopontin Splice Variantsevidence For Association With Spementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, OPN precursor mRNA undergoes alternative splicing leading to full-length OPN-a (i.e., consist of all exons), OPN-b (lacks exon 5) and OPN-c (lacks exon 4) as well [20]. The OPN splice variants are differentially expressed and may have functional heterogeneity in tumor specific manner [21] and recently are beginning to be studied in other diseases as calcific aortic valve disease [22], carotid atherosclerotic plaques [23] and systemic inflammatory conditions [24]. We have hypothesized that OPN isoforms and thrombin mRNA profile underlies the occurrence of pro-remodeling or pro-repair phenotype in endstage failing heart of different origin.…”
Section: Introductionmentioning
confidence: 99%